Peran CSR Terhadap Peningkatan Mutu Pendidikan Dasar 9 tahun - Limbong, Mesta (Journal of Education Research in Administration and Management (JERAM), 2017)
This research was carried to look at the quality of the 9-year primary education at the primary schools under the responsibility of PT Windu Nabatindo Lestari Bumitama Gunajaya Agro , a palm oil plantation in Central Kalimantan. The four standards measured are (1) competence of the graduates, (2) teachers and supporting staff, (3) facilities and infrastructures, and (4) costs. The company is responsible for increasing the standard quality of education within the plantation through its Corporate Social Reaponsibility (CSR) which targets education in the platation areas. This research uses qualitative method; data collection was done through observation, interviews, school documents, database, and note taking. The results shows that not all minimum indicators of the standards met the requirements, such as, there was no career tracks for teachers and supporting staff, budget was allocated more on operational coats. Facilities ad infrastructures were far from adequate for a quality education.